PENGARUH KEWIRAUSAHAAN, KEPEMIMPINAN DAN PELATIHAN TERHADAP KINERJA UMKM DI PALEMBANG - Lusia Nargis (Fakultas Ekonomi Universitas Tridinanti Palembang, 2016)
This research is intended to analyze the influence of enterpreneurship, leadership and trainning to micro, small, and middle business (UMKM) performance in Palembang city. This research is focused manufacturing industry sector and has gotten training from Dinas Perindustrian, Perdagangan dan Koperasi kota Palembang in 2012. UMKM that has gotten training are 51 units and only 41 unit that are choosen to be samples. The data is collected by giving questionnaire by using Likert scale and has been through validity and realibility test before. Data Analysis Method uses Multiple Regression Analysis with Ordinary Least Square.The result of this research shows that : Y= 15.246 + 0.221X1 + 0.238 X2+0.369X3, where X1= Entrepreneurship, X2= Leadership, X3= Training. Entrepreneurship influences the performance for 22.1 %, leadership influences the performance for 23.8%, and training influences the performance for 36.9%. From those 3 variables, training influences the performance the most. According to F-test is 14.143 and it’s bigger than F-table which is only 4.08. It shows that entrepreneurship, leadership, adn training influence the performance of UMKM simultaneously for 14.143%. And according to Determination Coefficient Test, it shows 0.475 which means that those three variables contribute to the dependent variables of UMKM performance for 47.5% and the rest for 52.5% is influenced from another variables that are not discussed in this research. From three variables are enterpreneurship, leadership and trainning, most influence to UMKM performance is trainning 36,9 percent. Key words : enterpreneurship, leadership, trainning, performance, small business, manufacturing industry